2006
DOI: 10.1530/rep.1.01128
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of healthy follicles in the neonatal and adult mouse ovary: evidence for maintenance of primordial follicle supply

Abstract: Proliferation and partial meiotic maturation of germ cells in fetal ovaries is believed to establish a finite, non-renewable pool of primordial follicles at birth. The supply of primordial follicles in postnatal life should be depleted during folliculogenesis, either undergoing atresia or surviving to ovulation. Recent studies of mouse ovaries propose that intra-and extraovarian germline stem cells replenish oocytes and form new primordial follicles. We quantified all healthy follicles in C57BL/6 mouse ovaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
180
2
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(206 citation statements)
references
References 85 publications
18
180
2
5
Order By: Relevance
“…Tissues were formalin-or Bouin reagent-fixed, processed, and stained with periodic acid-Schiff reagent/hematoxylin (19). Testis tubule and ovarian follicle counts were calculated as described previously (14,44).…”
Section: Methodsmentioning
confidence: 99%
“…Tissues were formalin-or Bouin reagent-fixed, processed, and stained with periodic acid-Schiff reagent/hematoxylin (19). Testis tubule and ovarian follicle counts were calculated as described previously (14,44).…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that the size of the primordial follicle reserve pool remains stable in adult C57BL/6 mice between the ages of 25 and 100 days (Kerr et al 2006). This plateau in numbers may indicate a very slow rate of primordial follicle recruitment, and limited loss of primordial follicles through death, such that a decline cannot be detected with the number of animals used or the statistical analysis applied (Faddy & Gosden 2007).…”
Section: Introductionmentioning
confidence: 90%
“…At least, "until someone comes up with some killer experiments to prove that bone marrow, or the ovary, is, or is not, the source of new oocytes". Kerr, Jock Findlay and colleagues add a piece of support for regeneration in research to be published online later this month 4 .…”
Section: Embryonic Ideamentioning
confidence: 99%